Does Economic Literacy Affect Inflation Expectations? An Experimental Survey Approach - KC, Irfan Ali (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
This study investigates the effectiveness of the information treatment in the inflation expectations on individuals with varying levels of economic literacy. In this regard, we conducted an experimental survey that provided participants with information related to inflation and other macroeconomic variables. The study reveals that the information treatment was effective in assisting the participants revise their expectations closer to actual inflation. Notably, this was especially effective for those without an economics background as they revised it to align with the actual inflation. Additionally, we found that formal economics learning is insignificant in the formation of inflation expectations given that the relevant information is accessible. Results of the study shed light on the importance of addressing information friction, focusing on financial education and effective communication from central banks.